Role of wholesale markets in fresh fruit and vegetable distribution in Hungary - Tenk, A.; Kalmár-Hollósi, E.; Kalmár, E. (International Journal of Horticultural Science, 2001)
The primer function of fruit and vegetable wholesale markets — which was the physical concentration of supply and demand previously — is changing gradually as consumer habits change and logistics functions (e.g. product manipulation, redistribution without the physical presence of the product) become more important with the technical development. Mainly individual growers sell their product to retailers at the Hungarian regional producers’ markets and the Budapest Wholesale market on NagykOrosi Street, which is the largest wholesale market in Hungary regarding area, produce arrival and turnover. Parallel to the establishment of Producers’ Organisations (P0) their market presence should be urged in selling their produce and also in ownership — and decision-making procedure — of the markets. The produce auction system and the on-line sales experiences of New Jersey State (USA) can contribute to the investigation of development possibilities and realization of development of Hungarian wholesale markets.